90-day Readmission in Elective Primary Lumbar Spine Surgery in the Inpatient Setting: A Nationwide Readmissions Database Sample Analysis. Issue 14 (15th July 2019) - Rubel, Nicolas C.; Chung, Andrew S.; Wong, Michael; Lara, Nina J.; Makovicka, Justin L.; Arvind, Varun; Chang, Michael S.; Cho, Samuel K.
Abstract : Study Design: Secondary analysis of a large administrative database. Objective: The objectives of this study are to: 1) identify the incidence and cause of 90-day readmissions following primary elective lumbar spine surgery, 2) offer insight into potential risk factors that contribute to these readmissions, and 3) quantify the cost associated with these readmissions. Summary of Background Data: As bundled-payment models for the reimbursement of surgical services become more popular in spine, the focus is shifting toward long-term patient outcomes in the context of 90-day episodes of care. With limited data available on national 90-day readmission statistics available, we hope to provide evidence that will aid in the development of more cost-effective perioperative care models. Methods: Using ICD-9 coding, we identified all patients 18 years of age and older in the 2014 Nationwide Readmissions Database (NRD) who underwent an elective, inpatient, primary lumbar spine surgery. Using multivariate logistic regression, we identified independent predictors of 90-day readmission while controlling for a multitude of confounding variables and completed a comparative cost analysis. Results: We identified 169, 788 patients who underwent a primary lumbar spine procedure. In total 4268 (2.5%) were readmitted within 90 days. There was no difference in comorbidity burden between cohorts (readmitted vs. not readmitted) as quantified by the Elixhauser Comorbidity index. Independent predictors of increased odds of 90-day readmission were: anemia, uncomplicated diabetes and diabetes with chronic complications, surgical wound disruption and acute myocardial infarction at the time of the index admission, self-pay status, and an anterior surgical approach. Implant complications were identified as the primary related cause of readmission. These readmissions were associated with a significant cost increase. Conclusion: There are clearly identifiable risk factors that increase the odds of hospital readmission within 90 days of primary lumbar spine surgery. An overall 90-day readmission rate of 2.5%, while relatively low, carries significantly increased cost to both the patient and hospital. Level of Evidence: 3 Abstract : With the increasing popularity of bundled payment models in spine, defining the 90-day postoperative course is of paramount importance. Using the National Readmissions Database (NRD), we identified predictors of 90-day readmission and defined the cost associated with readmission after elective primary lumbar spine surgery in the inpatient setting.